2010
DOI: 10.1002/pd.2514
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of severe thalassemia in northeast Thailand: 16 years of experience at a single university center

Abstract: Implementation of a prevention and control program accompanying with a referral system for prenatal diagnosis is technically feasible in northeast Thailand and a large number of severe thalassemia diseases have been prevented during the past 16 years of operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 23 publications
3
80
0
1
Order By: Relevance
“…Hemoglobin (Hb) E-β-thalassemia is the most common form of thalassemia found in Northeast Thailand [1,2]. The phenotypic expression of this disease can vary from mild thalassemia intermedia to severe transfusion-dependent thalassemia, and β-thalassemia mutation type has been found to be the primary factor determining disease severity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobin (Hb) E-β-thalassemia is the most common form of thalassemia found in Northeast Thailand [1,2]. The phenotypic expression of this disease can vary from mild thalassemia intermedia to severe transfusion-dependent thalassemia, and β-thalassemia mutation type has been found to be the primary factor determining disease severity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Hb analyses demonstrated a major peak of Hb Tak (91.9 %) and increased Hb A 2 (5.4%) but no Hb A. Screening for β-thalassemia mutations commonly found in our region [16,17] yielded a negative result. DNA analysis by allele-specific PCR revealed homozygosity for the Hb Tak mutation and a coinheritance of the 3.7-kb deletional α + -thalassemia determinant.…”
Section: Resultsmentioning
confidence: 99%
“…However, cordocentesis is still a relevant practice at our center especially for late pregnancies or when the parents' mutations are not known. At our center, a previous study has demonstrated that approximately 22.2% of prenatal diagnosis was done by cordocentesis [12]. The fetal blood specimens obtained with this practice gave us the chance to examine the fetal RBC parameters associated with various thalassemia syndromes thanks to the availability of an automated blood cell counter which can utilize a small volume of blood for analysis.…”
Section: Discussionmentioning
confidence: 99%